WAYANG GAMBUH AS A REPRESENTATION OF BALINESE CULTURAL VALUES: AN AESTHETIC PERSPECTIVE ON THE PERFORMING ARTS - I Made Marajaya (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2026)
Wayang Gambuh is a form of Balinese shadow puppet theater rich in aesthetic and cultural-philosophical values. This performance has its roots in the Gambuh dance-drama, so the essence of Gambuh is strongly felt in every performance. The aesthetics of Wayang Gambuh are reflected through the elements that form the structure of the performance, such as the narrative, the visual imagery, the characterization, and the accompanying music in the form of the Gambuh gamelan. This study aims to analyze the aesthetics of Wayang Gambuh as a representation of Balinese cultural values from the perspective of performing arts. As a hybrid of the Gambuh dance-drama, Wayang Gambuh is often perceived as complex and difficult to master by aspiring puppeteers. However, this is not the case. Unlike Wayang Arja, which follows the patterns of Arja dance-drama, Wayang Gambuh retains the structure of traditional wayang kulit performances, though its aesthetic nuances differ due to the accompaniment of Gambuh gamelan. The research findings indicate that Wayang Gambuh follows the structure of traditional wayang kulit performance art, such as Wayang Parwa, in a complete and dynamic manner. The audio-visual components including vocal performances, visual effects, characterization, and musical accompaniment blend into a symbolic unity that represents the values of harmony, artistry, aesthetics, and spirituality within Balinese society. Wayang Gambuh serves not only as entertainment but also as a medium for cultural and spiritual education that strengthens the identity of the Balinese people. This research is expected to open up broader avenues of study for researchers and enthusiasts of traditional art to re-examine the aesthetic elements of Wayang Gambuh, while also encouraging the preservation and development of this art form so that it remains relevant amidst the changing times.